The occurrence of antibiotic resistant Salmonellas in sewage and the effect of primary sedimentation on their numbers - Yaziz, Mohammad Ismail (Universiti Pertanian Malaysia, 1981)
The widespread use of antibiotics has led to the occurrence of resistant strains of bacteria in sewage and in the aquatic environment. This study has shown that there is no significant change in the proportion of antibiotic-resistant and antibiotic sensitive salmonellas during sedimentation of sewage and hence these organisms must have acquil·ed resistance during the initial use of the antibiotic and not during sewage treatment. Primary sedimentation alone can remove more than 80% of the total salmonellas present in raw sewage but negligible reductions will occur if the process is not optimised. The best way of controlling the release of antibiotic resistant salmonellas into the environment is to control the prescription and use of antibiotics.